Polyphasic characterization and GC-MS metabolite profiling of a Streptomyces isolate affiliated with Streptomyces hygroscopicus from pineapple rhizosphere in Lampung, Indonesia - TITIK NUR AENY; SELVI HELINA; HAMIM SUDARSONO; NI KADEK EMI SHINTA DEWI; SUSKANDINI RATIH DIRMAWATI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Aeny TN, Helina S, Sudarsono H, Dewi NKES, Dirmawati SR. 2026. Polyphasic characterization and GC-MS metabolite profiling of a Streptomyces isolate affiliated with Streptomyces hygroscopicus from pineapple rhizosphere in Lampung, Indonesia. Biodiversitas 27 (3): d270340. https://doi.org/10.13057/biodiv/d270340. Members of the genus Streptomyces represent taxonomically diverse and metabolically versatile actinobacteria commonly associated with rhizosphere ecosystems. This study presents a polyphasic characterization of a Streptomyces isolate obtained from the pineapple (Ananas comosus) rhizosphere in Lampung, Indonesia, integrating morphological, molecular, and metabolite profiling approaches. Morphological examination using scanning electron microscopy revealed extensively branched vegetative hyphae and rectiflexibiles-type spore chains with smooth surfaces, consistent with diagnostic features of the genus. Molecular identification based on 16S rRNA gene sequencing (~1,450 bp) placed the isolate within the Streptomyces hygroscopicus clade (GenBank accession no. PZ049818), showing low genetic divergence (<0.02 substitutions per site) relative to closely related strains, although species-level resolution remains limited using 16S rRNA alone. Gas Chromatography-Mass Spectrometry (GC-MS) analysis of ethyl acetate extracts detected 53 volatile and semi-volatile compounds, with similarity indices ranging from 66% to 96%; compounds with similarity indices ≥80% were considered reliable identifications. Major constituents included 3-deoxy-D-mannoic lactone (6.92%), (S)-(+)-2-amino-3-methyl-1-butanol (6.42%), 2-methylbutanoic anhydride (5.74%), catechol (5.16%), and 9,12-octadecadienoic acid (Z,Z) (4.58%), representing diverse chemical classes such as organic acids, alcohols, phenolics, and fatty acids. Although limited to a single isolate and qualitative metabolite profiling, this study provides baseline taxonomic and metabolomic data for pineapple-associated Streptomyces, serving as a foundation for future genomic, functional, and biocontrol-related studies in tropical agroecosystems.